Impact of railway station on Dutch residential housing market - Ghebreegziabiher Debrezion; Eric Pels; Piet Rietveld (European Regional Science Association (ERSA), 2005)
In an efficient market, the levels of house prices reflect the values of value of physical, accessibility and environmental features corresponding to the house. The Dutch residential house market though could not be claimed to work under a perfectly efficient market; the prices can be diagnosed to reflect the value of these features. This paper focuses on the value of railway accessibility feature to the residential houses prices. Stations are treated as transport access points with distance and frequency of train services components and potential places for negative externalities. Applying a cross sectional hedonic price model, we found railway stations as identified by frequency of train service has elasticity of close to 0.3 for house up to a distance of 3 kms. Due to the spatial nature of the data we controlled the spatial effects by regional dummies. Proximity to railway line as differing from proximity to station, explaining the noise effect, has negative effect on prices. At the same time the immediate neighbourhood of the station is affected negatively from externality of the station. Highway accessibility on the other hand shows slightly different effect on house prices, in that peak effects occur at 4-5 km from the highway entry/exit point. All other physical and neighbourhood variables as income level and population composition show expected effect on house prices.
Keywords: 330